Vibrational analysis of isonicotinamide - Akalın, Elif; Yılmaz, A.; AKYÜZ, SEVİM (Elsevier, 2005)
The FT-IR and FT-Raman spectra of isonicotinamide (in solid phase) have been recorded in the regions 4000–400 and 4000–70 cm−1, respectively. The geometry optimizations and vibrational spectrum calculations of isonicotinamide have been carried out at the DFT/B3LYP level with 6-31++G(d,p) basis set. With the SQM approach, the force field of isonicotinamide obtained by DFT calculations has been corrected by a set of scaling factors to get a good agreement between observed and calculated wavenumbers. Isonicotinamide interacting with Al(OH)3 has also been studied by B3LYP/6-31++G(d,p) calculations and the SQM results of both molecules have been compared to investigate how the coordination through the ring nitrogen effects the isonicotinamide vibrational wavenumbers.
Keywords: Coordinated isonicotinamide; DFT calculations; Isonicotinamide; SQM force field; Vibrational spectra